DESAIN KURSI GAMPSEK (GAMPIL LAN SEKECO) KONSEP PORTABLE FOLDING UNTUK ACARA TALK SHOW - Henny Tri Hastuti Hasana; Benny Febriyantoro; Marwahyudi (Universitas Sahid Surakarta, 2022)
Konsep Portable Folding. Gampsek chair is a chair for users in carrying out talk shows. The objective of writing this article is a) Being able to create a Gampsek Chair Design with Portable Folding Techniques. b) Able to make the proper choice of Material for Gampsek Chairs. Methods of data collection through observation, interviews, documentation, and literature study. The results of the data collection method show that the portable folding concept is suitable to be applied to Gampsek chairs. The portable folding concept is applied to the mainframe, seat, and armrests, and it can use a folding construction. Therefore, the chair looks compact, and it does not take up much space. This chair can make it easier for users when used in many places. The selection of materials is solid wood with natural finishing, hollow iron finishing with white color, and synthetic rattan so that the combination of materials makes the chair seem futuristic.